Comparison of peptide and superantigen-induced anergy in a peptide-specific polyclonal human T cell line. - Chu, N; Quaratino, S; Feldmann, M; Londei, M (1995)
T cells recognizing tetanus toxin peptide 'p2' (sequence 830-844) raised in HLA DR6 individuals preferentially express V beta 2 in the TCR. A p2-specific T cell line (60% V beta 2+) was used to compare peptide and superantigen [toxic shock syndrome toxin-1 (TSST-1)]-induced clonal anergy. Many experiments consistently revealed that the degree of 'tolerance' or 'clonal anergy' induced by peptide was greater than with the superantigen TSST-1. These results are of interest in a number of contexts. First they suggest that using superantigens or anti-V beta to delete the majority population of T cells may not be sufficient to diminish an autoimmune response. Secondly, the results indicate that induction of anergy of a large proportion of peptide-specific T cells does not lead to a suppressive bystander effect on the remaining responsive T cells. These results emphasize the need to define the dominant autoantigenic epitopes in human autoimmune diseases, since peptide based therapy such as the use of peptide analogues to induce anergy or a change in cytokine profile, is possibly more effective in controlling undesired immune responses than the use of non-antigen, TCR-directed approaches such as superantigens.